35. KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING MEDICAL INCIDENT REPORTING AMONG NURSES AND MIDWIVES IN SELECTED CLINICAL DEPARTMENTS OF VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge, attitudes, and practices regarding medical incident reporting among nurses and midwives in selected clinical departments of Vinmec Times City International General Hospital in 2025.Method: A cross-sectional descriptive study was conducted with 254 nurses and midwives from December 2024 to March 2025 in selected clinical departments at Vinmec Times City International General Hospital.Results: The rate of nurses and midwives regarding medical incident reporting with knowledge was 65.4%, good attitude was 92.5% and good practice was 82.7%, of which the rate of nurses and midwives answering correctly about the definition of medical incidents was 65.4%; 94.5% of nurses and midwives said that reporting incidents helps to learn from experience better among colleagues, helps to avoid repeating similar incidents and prevent errors better. The rate of nurses and midwives who practiced medical incident reporting was 83.5%.Conclusion: The rate of nurses and midwives with knowledge about rmedical incident reporting was still limited, so it is necessary to increase more training courses for health workers, focusing on basic knowledge about medical incidents as well as the importance of reporting medical incidents.
Keywords: Reporting; medical incidents; knowledge; attitude; practice.